ChemInform Abstract: A Terbium Rich Orthoborate LiSrTb2(BO3)3 and its Analogues. Issue 6 (21st January 2016) - Chen, Pengyun; Xia, Mingjun; Li, R. K.
Abstract: Single crystals of LiSrTb2 (BO3 )3 are grown by heating a 1:12:12:6 molar mixture of Tb4 O7, SrCO3, H3 BO3, and Li2 CO3 (Pt crucible, 950 °C, 1 d; cooling to 500 °C at a rate of 1.5 °C/h).